KONTRAK PERDAGANGAN MELALUI INTERNET (ELECTRONIC COMMERCE) DITINJAU DARI HUKUM PERJANJIAN - roida; Michael Ntuacademy (Nommensen Journal of Legal Opinion, 2022)
This research aims to determine the legal aspects of contracts in trading via the internet (e-commerce) in terms of contract law, as well as to determine the factors driving and inhibiting the implementation of e-commerce so that solutions can be found to problems in e-commerce contracts. This research, seen from its objectives, includes a descriptive type of normative legal research using qualitative methods. Data sources come from secondary data sources, namely literature, regulations, reports, archives and the internet. After the data was obtained, qualitative data analysis was carried out using non-statistical analysis. Based on the results of the research and data analysis that has been carried out, it can be seen that contracts in trading via the internet (e-commerce) have fulfilled several legal aspects of agreements in Book III of the Civil Code regarding the legal requirements, namely the agreement of the parties, a certain matter and the reasons why halal, even though it flows towards the element of maturity as a requirement for skill to enter into an agreement cannot be fulfilled, contracts in e-commerce are still valid and binding and become law for the parties who make them as long as the parties do not dispute it. This is because the skill requirement to enter into an agreement is a subjective requirement, which means that even if the skill requirement is not met, the contract in e-commerce made and agreed upon by the parties is still valid, but as a result of the contract, one of the parties can request an exemption. Apart from that, contracts in e-commerce fulfill the principles of agreement in the Civil Code. As well as the existence of factors encouraging and inhibiting the implementation of trading via the internet and also solutions to problems that arise in trading contracts via the internet (e-commerce). Solutions to problems arising from contracts in e-commerce such as authenticity, legality, data confidentiality can be overcome by the use of cryptography, digital signatures (digital signatures). Apart from that, the problem of announcing the choice of law can be overcome by using The Most Characteristic Connection, which means that the law used is the law of reporting the most prestige.